2020
DOI: 10.1038/s41467-020-17871-5
|View full text |Cite
|
Sign up to set email alerts
|

Gsta4 controls apoptosis of differentiating adult oligodendrocytes during homeostasis and remyelination via the mitochondria-associated Fas-Casp8-Bid-axis

Abstract: Arrest of oligodendrocyte (OL) differentiation and remyelination following myelin damage in multiple sclerosis (MS) is associated with neurodegeneration and clinical worsening. We show that Glutathione S-transferase 4α (Gsta4) is highly expressed during adult OL differentiation and that Gsta4 loss impairs differentiation into myelinating OLs in vitro. In addition, we identify Gsta4 as a target of both dimethyl fumarate, an existing MS therapy, and clemastine fumarate, a candidate remyelinating agent in MS. Ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…Experimental details for our material are summarized in Table 2. Lysolecithin injections in the cervical spinal cord were performed as previously described (Blakemore & Franklin, 2008; Carlström et al., 2020; Ineichen et al., 2017): briefly, rats were deeply anesthetized under fentanyl, medetomidine, and midazolam (for Lewis rats) or isoflurane (for Dark agouti rats). Lysolecithin solution (1% in injectable water) was stereotactically injected to either the dorsal funiculus of the cervical spinal cord level C3 (Lewis) or the CC (Dark agouti).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental details for our material are summarized in Table 2. Lysolecithin injections in the cervical spinal cord were performed as previously described (Blakemore & Franklin, 2008; Carlström et al., 2020; Ineichen et al., 2017): briefly, rats were deeply anesthetized under fentanyl, medetomidine, and midazolam (for Lewis rats) or isoflurane (for Dark agouti rats). Lysolecithin solution (1% in injectable water) was stereotactically injected to either the dorsal funiculus of the cervical spinal cord level C3 (Lewis) or the CC (Dark agouti).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the intracellular threats, extracellular ROS released by pro-inflammatory cells, such as microglia and macrophages, can attack neighbouring OPCs/oligodendrocytes [106,107]. It is important to note that the effect of ROS in circulating or infiltrating immune cells depends on the site of production, especially in case of autoimmunity where ROS induce Treg activation while limiting T cell proliferation and cytokine production [108][109][110][111], resulting in dampened disease activity. Similarly, increased ROS generation by peripheral blood monocytes via NOX3 is associated with better response to dimethyl fumarate in MS patients.…”
Section: Physiology and Sources Of Oxidative/nitrosative And Carbonylmentioning
confidence: 99%
“…The GST ∏ isoenzyme has been detected as a marker for mature oligodendrocytes that is absent in OPCs [147][148][149]. Moreover, recent studies identified an additional isoenzyme, GSTα4, to do play a role in OPC differentiation and protection against HNE [109]. In line with possessing a threefold lower basal level of GSH compared to astrocytes, OPCs are more vulnerable to GSH depletion [141,150,151].…”
Section: Endogenous Defence Mechanisms and Opc Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In two placebo-controlled phase III trials, 240 mg of DMF taken twice daily reduced ARR with 45 and 53%, respectively [127,128]. The mechanism of action of DMF includes effects on nuclear factor erythroid 2related factor 2, a transcription factor involved in cellular redox reactions, and an increase in oxidative responses in myeloid cells, in turn downregulating activated lymphocytes [66,129]. Flushing, abdominal pain, diarrhoea and nausea are common and have a negative effect on tolerability.…”
Section: Fumaratesmentioning
confidence: 99%